EFFORTS TO IMPROVE ACTIVENESS AND LEARNING OUTCOMES THROUGH SPIN WHEEL LEARNING MEDIA IN PANCASILA LESSONS FOR GRADE II ELEMENTARY SCHOOL STUDENTS - Syafiqah Rahadatul Aisy; Devina Tri Utary; Keiza Rizkia Audina; Nabila Azahra; Mawardi (Journal Informatic, Education and Management (JIEM), 2026)
- This research aims to improve the involvement and learning outcomes of elementary school second-grade students in Pancasila subjects through the application of the "Spin Wheel" learning media, which is based on Jean Piaget's theory of cognitive development. Carried out as Class Action Research (PTK), this research includes two cycles each consisting of four stages: planning, implementation of actions, observation, and reflection. The subjects of the study were second-grade students, with evaluations focusing on process data (student involvement) and learning outcome data. The results showed that Spin Wheel media significantly improved teacher activity, student engagement, and learning outcomes. In Cycle I, the average rate of implementation of teacher actions reached 82.82%, while student involvement was at 48.13%. After reflection and improvement in classroom management, the implementation of teachers' actions reached a perfect score of 100.00% in Cycle II, and the average student involvement increased sharply to 86.88% (reaching a peak of 90.00% in the second meeting). Increased involvement in this learning process has a direct impact on learning outcomes; the percentage of students who met the Learning Goal Achievement Criteria (KKTP ≥ 6.5) managed to exceed the success indicator by 80%. Thus, the Spin Wheel media has proven to be effective in transforming abstract Pancasila concepts into concrete, visual, and interactive elements, in line with the characteristics of the concrete operational thinking stage in children aged 7 to 8 years.